Inkludierte Exkludierte Studentische Verhandlungsweisen von Rassismus und Rassismuserfahrungen - Popal-Akhzarati, Karima (Universitätsverlag Göttingen, 2019)
Racism as a historically grown power relation varies in its complex configurations, depending on social-political as well as local-historical contexts. This study examines how students deal with racism, with a particular focus on the contexts and institutions of academia. Due to the adaptive potential of current forms of racism, paradox spheres (of negotiation) open up to those affected by it: On the one hand, as academics, they are included, however, in a limited way, while on the other hand they remain excluded due to their ongoing experiences of being othered. The analyses show that the social and institutional handling of racism and experiences of racism are mostly tabooed or de-thematized. These structural circumstances fundamentally affect the students' handling of racism.